2021
DOI: 10.36849/jdd.6263
|View full text |Cite
|
Sign up to set email alerts
|

AbobotulinumtoxinA for the Treatment of Moderate-to-Severe Glabellar Lines: A Randomized, Dose-Escalating, Double-Blind Study

Abstract: Objective: To evaluate the efficacy and safety of AbobotulinumtoxinA (ABO) dose escalation in the correction of moderate-to-severe glabellar lines. Design: Phase 2, 36-week, multicenter, randomized, dose-ranging, double-blind, placebo-controlled study. Methods: Adults with moderate-to-severe glabellar lines received a single ABO treatment, dosed at 50, 75, 100, or 125 U, or placebo. Primary endpoint was week 4 composite ≥2-grade responder rate among those achieving a severity score of 0 (none) or 1 (mild) at m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 14 publications
7
22
0
Order By: Relevance
“…The main results of the study, reported by Joseph et al, revealed a tendency toward higher response rates, with subjects achieving ≥2‐grade improvements alongside severity scores of 0 (none) or 1 (mild), and longer duration of aesthetic effect with increasing ABO dosage when assessed over a 9‐month period 21 . Incidence of adverse events was consistently low across all ABO doses and comparable with the literature regarding safety with the licensed dose 3‐13,21 . Here, we report subject self‐assessment of efficacy, as well as satisfaction and FACE‐Q data from the same ABO dose‐ranging study with the aim of advancing understanding regarding the relationship between treatment efficacy, satisfaction, and psychological well‐being with escalating ABO dose 21 .…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…The main results of the study, reported by Joseph et al, revealed a tendency toward higher response rates, with subjects achieving ≥2‐grade improvements alongside severity scores of 0 (none) or 1 (mild), and longer duration of aesthetic effect with increasing ABO dosage when assessed over a 9‐month period 21 . Incidence of adverse events was consistently low across all ABO doses and comparable with the literature regarding safety with the licensed dose 3‐13,21 . Here, we report subject self‐assessment of efficacy, as well as satisfaction and FACE‐Q data from the same ABO dose‐ranging study with the aim of advancing understanding regarding the relationship between treatment efficacy, satisfaction, and psychological well‐being with escalating ABO dose 21 .…”
Section: Introductionmentioning
confidence: 84%
“…The primary endpoint was composite ≥2‐grade responder rate at Week 4 in those achieving a severity score of 0 (none) or 1 (mild) at maximum frown, evaluated using concurrent ILA and SSA scales (reported in Joseph et al) 21 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the reported duration for time to loss of none or mild of ABO 50U for GL in the pivotal studies ranged from 85 to 119 days compared to the ≈168 days reported for the same dose and reconstitution scheme for the 50U dose in the ABO HD study. 5 , 6 , 10 Given these large discrepancies from the pivotal data, we find it hard to accept the findings from the ABO HD study. While this was not addressed in the article, we feel it is worthy of discussion.…”
mentioning
confidence: 89%